Analysis of Diabetic Footballers Blood Sugar Levels - János TÓTH Jr.; Ádám SZÁNTAI-KIS (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae)
Diabetes is one of the fastest growing diseases of our time. (Bakó, 2022) Nowadays 64 million people are diagnosed with diabetes and this number is rising with high tendency. (WHO, 2024) Furthermore lots of people do not know about their diabetes, so this number is not the exact one, it is a lot higher. In Hungary 1,2 million people were diagnosed with diabetes and a bit more of 39.000 people got type one diabetes. (Hungarian Government, 2024) We know about some methods to keep these people healthy and one of them is to do some exercise but also must pay attention to eat healthy and the most important one is the insulin supplement. Luckily, we got some tools like Continuous Glucose Monitoring sensors (CGM), insulin pumps which help us to control diabetes easier. Football has many effects on blood sugar levels. In our research we investigate these. The effects of a training session or a match on the blood sugar levels. Our hypotheses are to watch the differences of training sessions and matches, and the athletes thinking of their performance, in particular their impact of diabetes. From our three hypotheses only one was true, but I have to mention that our population was only ten people, therefore, if we got a chance to examine a bigger population maybe we would have got different results. Because of the rise of this disease in the future we can work with a lot more diabetic athletes in this sport like Nacho Fernandez, former Real Madrid defender (Somfai, 2018). This research can be useful for many coaches and also can help to prepare to work with diabetic players.